POLITIK HUKUM KEBIJAKAN PEMERINTAH DALAM MENJAGA MUTU PENDIDIKAN NASIONAL PADA TINGKAT PERGURUAN TINGGI DI MASA PANDEMI COVID-19 - Tua, Guido Gomgom; Artina, Dessy; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Covid-19 is a global pandemic and a global health problem. The great threat of the Covid-19 pandemic is a test for the government of every country in fighting it, whether sooner or later, efficient or inefficient, effective or ineffective. The 1945 Constitution of the Republic of Indonesia has placed the law in a supreme and decisive position in the Indonesian constitutional system. So that all actions taken by the government must have a legal basis. In maintaining the quality of education at the tertiary level during the Covid-19 pandemic, the government issued a legal policy in the form of joint decrees and circulars in which it hopes to maintain the quality of education during the Covid-19 pandemic. The purpose of writing this thesis, namely: first, to find out the legal politics of government policies in maintaining the quality of national education, especially at the university level during the Covid-19 pandemic. Second, to find out the ideal concept of government policy in maintaining the quality and/or improving the National education system, especially at the Higher Education level during the Covid-19 Pandemic.This type of research can be classified in the type of juridical normative research, because in this study in addition to using secondary data, the authors also conduct interviews to provide an overview of the problems studied. Sources of data used are primary data and secondary data. In this paper using qualitative data analysis which means explaining and concluding about the data that has been collected by the author. through literature that investigates and takes an inventory of legal materials with documents, literature books, legal journals, laws and interviews related to the object of research.The results of the research and discussion can be concluded: first, that the Covid-19 pandemic requires learning that was originally offline to be online, in this case the government issues policy regulations which are the result of legal politics to help carry out online education during the Covid-19 pandemic. Second, because the policy regulations do not have legal force and the resolution of the Covid-19 pandemic is not yet clear, therefore ideally the government should make the Covid-19 pandemic the basis for forming statutory regulations and/or revising existing laws.Keywords: Education - Higher Education - Covid-19 Pandemic